Potencial erosivo das chuvas e qualidade da água drenada sob diferentes coberturas de solo em simulador portátil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Erosion caused by water occurs in three phases: destruction of soil aggregate structure, transport, and deposition of sediments in topographically lower areas of a landscape. The objective of this research was to estimate the erosive potential of rainfall through the use of a portable simulator incorporating different soil vegetation covers, and subsequently to evaluate the responses of thermographic and physical and chemical indicators under ambient climate conditions in Belterra, State of Pará. Rainfall data from 1972 through 2017 were obtained from the database of the National Institute of Meteorology (INMET), and these data were used to estimate the erosive potential of this rainfall on annual and monthly scales. The rainfall coefficient (Rc), erosivity, and Rainfall Anomaly Index (IAC) were evaluated using these data. Furthermore, rainfall data from the months of January and February 2018 were analyzed in order to identify rainfall events that occurred during the field evaluation period using the portable simulator. During the simulations three types of rainfall events were considered (weak, moderate, and intense), testing the effects under three conditions: exposed soil, soil covered with garden of grass, and soil covered with lettuce. During the simulations the volume of water drained into each recipient of the simulator was quantified in order to evaluate the losses of soil solution, and one liter of this water was retained for laboratory physical and chemical analyses. A thermographic camera was used to take near infrared images in the area near and around the simulator including the simulator roof and the three treatments. The thermal patterns were treated with the FLIR Tools computational program. The results showed that the year 1985 had the highest rainfall (3,057.0 mm), and the year with the least rainfall was 1992 (974.2 mm). Annual average erosivity was on the order of 13,000 MJ mm ha-1 h-1 year-1, indicating a high erosive potential in Belterra. During La Niña years in which the rainfall anomalies were positive and exceeded climatological norms, problems due to erosion intensified. Among the physical and chemical parameters verified, calcium (20.8 mg L-1), turbidity (1100 UNT), suspended solids (4.265 mg L-1), and magnesium (37.44 mg L-1) were the ones that showed the largest effects. The portable rainfall simulator increased the awareness of the extensionists, students, professors, and farmers that participated in the trials, and allowed them to be able to witness first-hand and verbalize the importance of this research that used practical examples in order to express complex processes such as erosion due to rainfall. The thermal patterns showed that for the lettuce soil cover the average temperature was 32.3°C, with reduced thermal amplitude of (0.1°C) at the end of the simulation. For the exposed soil and the grass-covered soil the amplitude reached 1.8°C, thus indicating rapid thermal changes after rainfall events. We conclude that in Belterra there is a high erosive potential which represents a threat to soil conservation. The portable simulator promoted increased awareness of soil loss due to erosion of uncovered soil among diverse social actors. The thermal diagnosis in real-time enabled the comparison and identification of different processes that occur at the moment of raindrop impact on the soil surface.
Keywords: Erosividade; Uso Antrópico; Precipitação Pluvial; Simulação; Sensibilização; Temperatura; CNPQ:: ENGENHARIAS